Handbook of Materials Failure Analysis 2018
DOI: 10.1016/b978-0-08-101928-3.00012-4
|View full text |Cite
|
Sign up to set email alerts
|

Consolidation works on sandstone monuments: A new approach

Abstract: Portugal is the home of some very important buildings and monuments where natural stone is the predominant material, for example, in castles, churches, and palaces. Sandstones use is common in traditional buildings in western regions of Portugal (Peniche and Lourinhã) and in Algarve (Silves). The International Council on Monuments and Sites-International Scientific Committee for Stone (ICOMOS-ISCS) [1] describes stone degradation patterns on monuments and ancient buildings. All of five families of ICOMOS-ISCS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…This first stage of consolidation works intended to assess the viability of future TEOS applications on these stone walls. Ludovico-Marques and Chastre (2014, 2016) [26,27] carried out experimental research on sandstone specimens similar to the stones of variety M in the monument, with circa 3-5 times the porosity values of varieties B and A. These products were applied by an initial immersion and capillarity procedure, followed by full immersion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This first stage of consolidation works intended to assess the viability of future TEOS applications on these stone walls. Ludovico-Marques and Chastre (2014, 2016) [26,27] carried out experimental research on sandstone specimens similar to the stones of variety M in the monument, with circa 3-5 times the porosity values of varieties B and A. These products were applied by an initial immersion and capillarity procedure, followed by full immersion.…”
Section: Introductionmentioning
confidence: 99%
“…As it is visible, alveolization is in an early stage in this lithotype. 2002) [27,28], showed detailed data of consolidating treatments through the application of a MTMOS product, Brethane, on cultural heritage sandstones (e.g., in castles and abbeys sites) with higher values of porosity. The study reported that Brethane did not perform well when the durability was assessed through the salt effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation